Step * of Lemma quadratic-formula2

a,b,c:ℝ.
  (a ≠ r0
   (r0 ≤ ((b b) r(4) c))
   (∀x:ℝ
        ((((a x^2) (b x) c) r0)
         ((¬¬((x quadratic1(a;b;c)) ∨ (x quadratic2(a;b;c))))
           ∧ ((((r(2) a) x) b ≠ r0 ∨ (r0 < ((b b) r(4) c)))
              ((x quadratic1(a;b;c)) ∨ (x quadratic2(a;b;c))))))))
BY
(RepeatFor ((D THENA Auto))
   THEN (Assert r(2) a ≠ r0 BY
               (RepeatFor (ParallelOp 4) THEN nRMul ⌜r(2)⌝ 4⋅ THEN Auto))
   THEN Unfolds ``quadratic1 quadratic2`` 0
   THEN (GenConclTerm ⌜rsqrt((b b) r(4) c)⌝⋅ THENA Auto)
   THEN (Assert (r0 ≤ v) ∧ ((v v) ((b b) r(4) c)) BY
               (D -2 THEN Unhide THEN Auto))
   THEN -1
   THEN RepeatFor ((D THENA Auto))) }

1
1. : ℝ
2. : ℝ
3. : ℝ
4. a ≠ r0
5. r0 ≤ ((b b) r(4) c)
6. r(2) a ≠ r0
7. {r:ℝ(r0 ≤ r) ∧ ((r r) ((b b) r(4) c))} 
8. rsqrt((b b) r(4) c) v ∈ {r:ℝ(r0 ≤ r) ∧ ((r r) ((b b) r(4) c))} 
9. r0 ≤ v
10. (v v) ((b b) r(4) c)
11. : ℝ
12. ((a x^2) (b x) c) r0
⊢ (¬¬((x (-(b) v/r(2) a)) ∨ (x (-(b) v/r(2) a))))
∧ ((((r(2) a) x) b ≠ r0 ∨ (r0 < ((b b) r(4) c)))
   ((x (-(b) v/r(2) a)) ∨ (x (-(b) v/r(2) a))))


Latex:


Latex:
\mforall{}a,b,c:\mBbbR{}.
    (a  \mneq{}  r0
    {}\mRightarrow{}  (r0  \mleq{}  ((b  *  b)  -  r(4)  *  a  *  c))
    {}\mRightarrow{}  (\mforall{}x:\mBbbR{}
                ((((a  *  x\^{}2)  +  (b  *  x)  +  c)  =  r0)
                {}\mRightarrow{}  ((\mneg{}\mneg{}((x  =  quadratic1(a;b;c))  \mvee{}  (x  =  quadratic2(a;b;c))))
                      \mwedge{}  ((((r(2)  *  a)  *  x)  +  b  \mneq{}  r0  \mvee{}  (r0  <  ((b  *  b)  -  r(4)  *  a  *  c)))
                          {}\mRightarrow{}  ((x  =  quadratic1(a;b;c))  \mvee{}  (x  =  quadratic2(a;b;c))))))))


By


Latex:
(RepeatFor  5  ((D  0  THENA  Auto))
  THEN  (Assert  r(2)  *  a  \mneq{}  r0  BY
                          (RepeatFor  2  (ParallelOp  4)  THEN  nRMul  \mkleeneopen{}r(2)\mkleeneclose{}  4\mcdot{}  THEN  Auto))
  THEN  Unfolds  ``quadratic1  quadratic2``  0
  THEN  (GenConclTerm  \mkleeneopen{}rsqrt((b  *  b)  -  r(4)  *  a  *  c)\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  (Assert  (r0  \mleq{}  v)  \mwedge{}  ((v  *  v)  =  ((b  *  b)  -  r(4)  *  a  *  c))  BY
                          (D  -2  THEN  Unhide  THEN  Auto))
  THEN  D  -1
  THEN  RepeatFor  2  ((D  0  THENA  Auto)))




Home Index